Job satisfaction of village doctors in a rural-oriented tuition-waived medical education program in China - Jin, Renmin; Chen, Yan (Frontiers in Psychology, 2023)
Introduction: To address health inequity and relieve shortage of rural doctors, China initiated Rural-oriented Tuition-waived Medical Education (RTME) to train doctors for rural areas for free since 2010. Little is known about job satisfaction of this particular group of rural doctors. Methods: Job Satisfaction Questionnaires for Village Doctors were distributed to 240 village doctors with RTME program in China, and 40 received in-depth semi-structured interviews. Descriptive analysis, chi-square test, univariate and multivariate logistic regressions in SPSS23.0 were conducted, and thematic analysis was applied to interviews. Results: Job satisfaction rate of village doctors with RTME program was 56.50%. Full understanding of RTME policy, recognition of rural medical work, relevance of RTME curriculum with present job, education background, rural origin and renumeration were positively correlated with job satisfaction. Preferential policies of RTME program, relaxing working atmosphere, more promotion opportunity, and easier access to higher technical title were the key factors to retain rural doctors. Conclusion: Our findings may interest healthcare authorities, medical colleges and primary healthcare establishments. Studying the job satisfaction of village doctors in China may also be beneficial in developing community and rural health services, and provide valuable insights into the training and retention of primary healthcare providers in other countries.